Double Russian Lexical Сopies in the Mari Lexicon - Agyagási, Klára (Slavica, 2018)
The author aims to reconstruct the phonetic, morphological, semantic and chronologicalpeculiarities of three pairs of Mari words (wočko and pečke ‘barrel’, kaďilä and ká·δәn ‘censer’,moľo and mŭľo ‘young fish’) borrowed from Russian dialects. She comes to the conclusionthat they can compose pairs as direct and indirect borrowings, different derivationalvarieties of the same verbal stem or the phonetically resembling Mari representations of twoetymologically different Russian dialectal words.